Improvement of Cu-Al bond integrity on low k pad structures - Kid W.B.; Leng E.P.; Yong C.C.; Yi O.X.; Kar Y.B. (2023)
Gold wires are commonly used for wire-bonding and it fits well the industrial requirements. However, the price of Gold wires increasing significantly, Copper wires is a potential replacement for Gold due to their superior electrical and mechanical properties. In order to incorporate Cu in the wire-bonding process, substantial data regarding aging and intermetallic formation of Cu-Al bonds is required and the results are compared with Au samples. In this study, the bond integrity and thermal aging of Cu-Al and Au-Al wire-bonds were investigated. The Copper and Gold wire-bonds samples were heat-treated at temperature of 225C for 4.5, 13.5, 26, 52 and 97 hours respectively. The intermetallics of the wire-bonds, and in particular the Al-Cu interface, were studied. Discontinuous and non-uniform of Cu-Al intermetallics regions were found in the thermal aging samples. The thickness of Cu-Al intermetallics is growing linearly with the temperature as the diffusion rate increases in higher temperature. The Cu-Al bond is weak compare to Au-Al in accordance with aging through wire pull test. 2011 IEEE.